If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 = 7 + m Solving 12 = 7 + m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-1m' to each side of the equation. 12 + -1m = 7 + m + -1m Combine like terms: m + -1m = 0 12 + -1m = 7 + 0 12 + -1m = 7 Add '-12' to each side of the equation. 12 + -12 + -1m = 7 + -12 Combine like terms: 12 + -12 = 0 0 + -1m = 7 + -12 -1m = 7 + -12 Combine like terms: 7 + -12 = -5 -1m = -5 Divide each side by '-1'. m = 5 Simplifying m = 5
| x^27=3 | | 72-3y-4y=32 | | 3(2*y+3)-4*y=-3 | | graphy=8.5x | | 55=-8a+63 | | (6x+3d)+(2x-d)= | | -5(3x-6)=120 | | 4p+3=9+3p | | 3x+77+4x+54=180 | | 33=-3(-8+x) | | -3(v+2)=-24 | | 24=1a | | 58=5u+13 | | 33=4x+4x-7 | | (12+9+12+9)12+2(12*9)= | | 5-(2x+1)=10-x | | 10=d+8 | | x^2+14x-52=0 | | 6(7+5x)=12 | | 4x+0.2+0.5=6 | | 7(3x-6)=-210 | | -2(a+2)=0 | | (6y+f)+(6y+f)+(6y+f)= | | 39=12z-18 | | 6x-2y-12=0 | | 5x(6+5y)= | | 9x+5y=180 | | a+(a+5)+(2a-10)=85 | | 48=3s | | .5n-10=4 | | 15+18+18+15+x=93 | | 1=-8c+9 |